Short Term Seasonalities on the Jakarta Stock Exchange - KUSNADI, Yuanto (Institutional Knowledge at Singapore Management University, 1999)
This research attempts to uncover the presence of various stock market seasonalities on the Jakarta Stock Exchange (JSX). We find that most of the seasonal effects exist on the JSX, except for the January effect. There is a day-of-the-week effect with low Tuesday and high Friday returns. The "twist" effect is confirmed with a negative Tuesday return following a market decline in the previous week. The Tuesday "Rogalski" effect is present, with Tuesday return being positive in the month of January and negative for the other months. The monthly, turn-of-the-month, turn-of-the-year and pre-holiday effects are also confirmed in recent sub-periods after the reforms of the JSX in 1988.